One-pot catalyst-free synthesis of benzopyrroxazine derivatives by a mutually activated sequential annulation process. Issue 23 (25th May 2022) - Li, Fu-Qiang; Xie, Pu-Yuan; Chen, Hui-Yu; Bian, Ming; Gao, Yu-Ning; Liu, Zhen-Jiang
Abstract : A one-pot catalyst-free synthetic method of benzopyrroxazine derivatives is reported, which relies on an efficient self-catalyzed [3 + 2] cycloaddition process. Abstract : A one-pot catalyst-free reaction of o -hydroxyaryl azomethine ylides, vinyl pyridines and paraformaldehyde for the synthesis of benzopyrroxazines is reported, which offers a straightforward and atom-economical procedure for the preparation of benzopyrroxazine derivatives in moderate to excellent yields under mild conditions. A self-catalyzed [3 + 2] annulation through a mutual activation method and a sequential non-catalyzed [5 + 1] annulation process contribute to this strategy. The corresponding control experiments have been conducted to reveal the mechanism of this reaction.